(3GdefGbUI GdYGeI cWQjbI ddJYGbO GdEOGQj aj GdbGfhf GdSYhOj (B: s (3OQGSI ebGQfI (B/ s - (3eMeO YHjO SYO GdSHjYj s; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3Ef ef GdCehQ GdJj JTZd Gdabg h GdbVGA ehVhY GdefGaSI GdYGeI (B( (3GdefGbUI GdYGeI (B): (3deGPG gPg GdWQjbI ef WQb GdJYGbO aj ETGYI GdKbI h GdTaGajI ddbGFejf Ydi MQGSI GdeGd GdYGe(B: (3h Ef cGfJ GdefGbUI GdYGeI bO dGbJ GdYfGjI ShGA ef LGfH GdeTQY GdeUQj(B: (3Ch ef LGfH Gdabg h GdbVGA Ydi hLg GdShGA(B: (3aEf Pdc GdCeQ dbi faS GdGgJeGe ef GdefXe GdSYhOj(B: (3h Pdc HEdZGA GdfXGe GdbOje(B: (3h gh fXGe eTJQjGJ GdMcheIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2011s
(3HHdjhLQGajG(B: (3UaMGJ (B158-165s
Keywords: (3GdbGfhf GdYGes; (3eGgjI GdefGbUI GdYGeIs; (3GdfXGe GdELQGFj s; (3GdefGbUGJ GdYGeI s; (3ELQGAGJ GdefGbUIs; (3VeGfGJ eQMdI Jbjje GdYWGAGJs; (3GdYWGAGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes